Assessing the structure and composition of artificial levees along the Lower Tisza River (Hungary) - Sheishah, Diaa; Sipos, György; Hegyi, Alexandru; Kozák, Péter; Abdelsamei, Enas; Tóth, Csaba; Onaca, Alexandru; Páll, Dávid Gergely (Geographica Pannonica, 2022)
Levees are earth structures constructed along alluvial rivers and are considered to be one of the essential components of flood risk and natural hazard reduction. The preservation of their condition would require orderly monitoring. In Hungary, an over 4200 km long levee system was constructed from the 19th century on. Since then, many natural and anthropogenic processes, such as compaction, erosion, subsidence etc., could contribute to the slow but steady deformation of these structures. In the meantime, due to the lack of documentation, their structure and internal composition are still unclear in many sections. The present study uses different geophysical techniques to validate their efficiency in detecting the structure, composition and potential defects along a 3.6 km levee section of the Lower Tisza River, affected significantly by seepage and piping phenomena during floods. Measurements were made using Ground Penetrating Radar (GPR), Electrical Resistivity Tomography (ERT) and drillings. Information obtained by the different techniques was cross-checked and combined. This way, the potential of the applied survey strategy could be demonstrated, and the selected levee section could be assessed in terms of its structure and composition. Consequently, the major reasons for frequently occurring adverse flood phenomena at the site could be revealed. The survey approach outlined in the present paper can be applied extensively along lowland levee systems in the region and elsewhere.